EFFICACY OF PERCUTANEOUS NEPHROLITHOTOMY IN HORSESHOE KIDNEYS: A COMPARISON OF MINI AND CONVENTIONAL APPROACHES (The Research of Medical Science Review, 2024)
Introduction: Renal stones, affecting 10% of the global population, are the most common urological condition with a high recurrence rate of 70%. Percutaneous nephrolithotomy (PCNL) is the standard treatment for renal stones larger than 2 cm, with the miniaturized variant (M-PCNL) being a less invasive alternative to conventional PCNL (C-PCNL). This study compares the efficacy and safety of M-PCNL and C-PCNL in managing renal stones in horseshoe kidneys. Materials and Methods: A randomized controlled trial was conducted at the Armed Forces Institute of Urology, Rawalpindi, involving 60 patients (30 in each group) with renal stones 2–4 cm in size. Participants were randomized to undergo either M-PCNL or C-PCNL. Stone-free status, complications, operative time, and hospital stay were compared between the two groups. Statistical analysis was performed using SPSS version 25, with significance set at p < 0.05.Results: The mean stone size was 1.59 cm in the M-PCNL group and 1.76 cm in the CPCNL group (p = 0.017). Stone clearance was 100% for M-PCNL and 96.7% for C-PCNL (p = 0.083). M-PCNL resulted in shorter hospital stays and reduced postoperative pain. Both techniques were highly effective, with M-PCNL demonstrating a slight advantage in safety and patient comfort. Conclusion: M-PCNL is a safe and effective alternative to C-PCNL for treating renal stones in horseshoe kidneys. It offers comparable stone clearance rates with reduced morbidity, making it a favorable option for patients. Overall there is no significant difference in efficacy of mini vs conventional PCNL. Further studies with larger sample sizes are recommended to validate these findings.